2019
DOI: 10.1039/c9nr00303g
|View full text |Cite
|
Sign up to set email alerts
|

New anionic poly(alkylideneamine) dendrimers as microbicide agents against HIV-1 infection

Abstract: This type of dendrimers, specifically the low-generation G1, can directly interact with the viruses, hampering their entry in the cells, preventing the HIV-1 infection without the need of combined therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 32 publications
0
25
0
1
Order By: Relevance
“…In the literature, there are several reports about the role of polyanions as entry inhibitors, especially against HIV infections (46,47). One of the main advantages of this interesting class over small-molecule drugs is their ability to bind to the target in a multivalent way, making them promising antiviral candidates (48). Comparison between our molecules and the established entry inhibitor DS (the control in this study) revealed numerous advantages, as AL439 and AL440 have a precise structure, welldefined composition, and moderate molecular size.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, there are several reports about the role of polyanions as entry inhibitors, especially against HIV infections (46,47). One of the main advantages of this interesting class over small-molecule drugs is their ability to bind to the target in a multivalent way, making them promising antiviral candidates (48). Comparison between our molecules and the established entry inhibitor DS (the control in this study) revealed numerous advantages, as AL439 and AL440 have a precise structure, welldefined composition, and moderate molecular size.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the dendrimers that may now be classified as “classic” include (i) poly(amidoamine) (PAMAM), which were developed by Tomalia in the 1980s, through an iterative reaction sequence between ethylenediamine and methyl ester moieties, and Michael addition with methyl acrylate on amines, in a divergent methodology [ 15 , 16 ]; and (ii) poly(ether), Fréchet dendrimers, prepared from 3,5-dihydroxy-benzyl bromide [ 17 ], in a convergent build-up on this core. Subsequently, several other interesting backbones of dendrimers/dendrons have been added [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ], and include some earlier reports on silicon-containing dendrimers by Hadjichristidis [ 28 ]; polylysine by Denkewalter [ 29 ]; polyester by Newkome [ 30 ] and Ihre et al [ 31 ]; phosphorus-containing dendrimers by Caminade and Majoral [ 32 , 33 , 34 ]; polyether dendrimer via OsO 4 catalyzed oxidation of carbon-carbon double bonds [ 35 ]; peptide dendrimers [ 36 ]; amphiphilic PAMAM dendrimer with one dendritic block functionalized with sugar and the other with N -phthalic amide moieties [ 37 ]; and dendrimers for one-pot post bis-functionalization [ 38 ].…”
Section: Dendrimers/dendronsmentioning
confidence: 99%
“…The therapeutic agents may either be encapsulated into the three-dimensional void spaces of the dendrimers or conjugated or physically adsorbed (electrostatic interactions) onto the surface of the dendrimer [ 11 , 12 ]. Another strategy is to develop dendrimers, such as drugs, active per se in several therapeutic realms [ [13] , [14] , [15] , [16] , [17] , [18] , [19] ]. Over the last several years, we have embarked on this direction in order to develop new drugs based on phosphorus dendrimers, for instance, as anticancer [ 20 , 21 ] and anti-inflammatory agents [ 22 ].…”
Section: Introductionmentioning
confidence: 99%